White wine processing by UHPH without SO2. Elimination of microbial populations and effect in oxidative enzymes, colloidal stability and sensory quality. (1st December 2020) - Bañuelos, Mª Antonia; Loira, Iris; Guamis, Buenaventura; Escott, Carlos; Del Fresno, Juan Manuel; Codina-Torrella, Idoia; Quevedo, Joan Miquel; Gervilla, Ramon; Chavarría, Jesús María Rodríguez; de Lamo, Sergi; Ferrer-Gallego, Raúl; Álvarez, Rocío; et al.
Highlights: Elimination of vegetative cells of yeast, molds and bacteria by UHPH in must. Strong inactivation of oxidative enzymes: PPO. Absence of thermal degradation markers. No detection of HMF. Higher antioxidant activity in UHPH processed must. UHPH is a powerful tool to reduce SO2 in white wines. Abstract: The use of UHPH sterilization in the absence of SO2 has been used to eliminate wild microorganisms and inactivate oxidative enzymes. A white must of the Muscat of Alexandria grape variety was continuously processed by UHPH at 300 MPa (inlet temperature: 23–25 °C). The initial microbial load of the settled must was 4-log CFU/mL for both yeast and moulds, and slightly lower for bacteria. After UHPH processing, no microorganisms were detected in 1 mL. UHPH musts remain without fermentative activity for more than 60 days. Concentrations of the thermal markers indicated the absence of thermal damage in the UHPH-treated musts, since 5-hydroxymethylfurfural was not detected. In addition, the must treated by UHPH keeps terpene concentrations similar to those of the untreated controls. A strong inactivation of the oxidative enzymes was observed, with no browning at room temperature for more than 3 days. The antioxidant value of the UHPH-treated must was 156% higher than the control.